Alignment : using the balanced scorecard to create corporate synergies - Kaplan, Robert S. (Harvard Business School Press, 2006)
"Most organizations contain multiple business and support units, each led by highly trained, experienced executives and staffed by talented employees. But too often, different units fail to coordinate: they work at cross-purposes and have conflicting goals. Results? Performance-sapping disagreements, lost opportunities, wasted resources - and a corporation whose value amounts to less than the sum of its parts." "Robert S. Kaplan and David P. Norton explain how to correct such organizational misalignment - not only within a company but between the firm and its board of directors, investors, customers, and suppliers."